Instant Automapper. - Bhatti, Taswar (Packt Publishing, 2013)
Get to grips with a new technology, understand what it is and what it can do for you, and then get to work with the most important features and tasks. This book is a practical, step-by-step tutorial that will enable you to use Automapper quickly and efficiently. Instant Automapper Starter is for .NET developers. A good background in .NET is assumed, but a novice user can follow along, and learn to become an advanced user of Automapper.